Aspects of Scientific Competences Outlined in High School Biology, Physics and Chemistry Syllabus and its Relation with the Scientific and Technological Development Needs of Costa Rica - Padilla-Canales, Cristina (2016)
The scientific and technological development of a country is directly linked to the strengthening of education in that field and the ability to brew advancement from the foundations of the education system. In this scenario, it was considered important to know whether the policies of scientific and technological development of Costa Rica relate to high school syllabus in the scientific area. Therefore, a qualitative research using a hermeneutic study was carried out. Nine participants (three biology teachers, three of physics, and three of chemistry) were selected from three kinds of educational institutions: academic, scientific and technical; as well as expert staff from the following entities: Ministry of Science and Technology, National Council of Scientific and Technological Research, Strategies for the 21st Century, Academy of Science, Center of Foreign Trade, INTEL and consultants of Biology, Physics and Chemistry from the Ministry of Public Education. The techniques used to collect information were: observation, content analysis and interviews. Among the main conclusions, it was found that biology syllabus is the one that best measures the dimensions (awareness of knowledge and knowledge to do, ability, attitude and context) from the evidenced competences through short-term expected capabilities, such as objectives, which suggests the articulation of these dimensions in each subject unit syllabus, a determining aspect to make high school education contribute to the scientific and technological development of the country. In addition, it was found, in general, that inside the classrooms there is a decontextualisation between what is taught and the development pursued by the policies in this field, because there is no connection between the educational plan intended in the syllabus and the scientific and technological development policies proposed in the country.